2019
DOI: 10.1002/ange.201905986
|View full text |Cite
|
Sign up to set email alerts
|

Electrophilic Iron Catalyst Paired with a Lithium Cation Enables Selective Functionalization of Non‐Activated Aliphatic C−H Bonds via Metallocarbene Intermediates

Abstract: Combining an electrophilic iron complex [Fe( F pda)-(THF)] 2 (3)[ F pda = N,N'-bis(pentafluorophenyl)-o-phenylenediamide] with the pre-activation of a-alkyl-substituted adiazoesters reagents by LiAl(OR F ) 4 [OR F = (OC(CF 3 ) 3 ]p rovides unprecedented access to selective iron-catalyzed intramolecular functionalization of strong alkyl C(sp 3 ) À Hb onds. Reactions occur at 25 8 8Cvia a-alkyl-metallocarbene intermediates,a nd with activity/selectivity levels similar to those of rhodium carboxylate catalysts.M … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…This contrasts with an experiment where TEMPO as a radical scavenger inhibits the reaction. However, it has been seen earlier that TEMPO can poison the metal‐porphyrin catalyst thereby inhibiting the reaction [36] …”
Section: Resultsmentioning
confidence: 99%
“…This contrasts with an experiment where TEMPO as a radical scavenger inhibits the reaction. However, it has been seen earlier that TEMPO can poison the metal‐porphyrin catalyst thereby inhibiting the reaction [36] …”
Section: Resultsmentioning
confidence: 99%
“…Four different chiral iodohydrocarbons are synthesized from corresponding chiral alcohol molecules by nucleophilic substitution (detail phase see Methods). 25 Then, such chiral alkyl chains are introduced into ted to form chiral quaternary ammonium salts, which serve as ligands combined with Cu-I inorganic modules by means of all-in-one typed coordinate bonds and ionic bonds together to construct chiral hybrid clusters. 22 All the synthetic organic compounds can be con rmed by 1 H NMR analysis (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In 2011 the definition of the hydrogen bond was proposed by IUPAC, 16 and on this basis an analogous definition of the lithium bond can be made. 17 Recently, a number of studies of Li-containing compounds have been reported, and these are related to many applications, such as lithium batteries, 18 lithium catalysts, 19,20 and organolithium chemistry. 21,22 The lithium bond is found to play important roles in these compounds.…”
Section: Introductionmentioning
confidence: 99%